PEMBERDAYAAN WANITA PKK DALAM MENGOLAH SIRUP ANTIOKSIDAN BERBAHAN LIMBAH KULIT MANGGIS - Ainol, Ainol; Qosim, Nanang (CV. Kalimasada Group, 2024)
This research aims to empower PKK women in processing mangosteen peel waste into antioxidant syrup that is beneficial to health. Mangosteen, in addition to being known as a delicious fruit, also has various health benefits contained in its fruit parts, especially its peel which is often neglected as waste. Mangosteen peel contains antioxidant compounds that can be used for various products, such as drinks and herbal medicines. Thus, this study raises the role of PKK women's empowerment in recycling mangosteen peel waste into antioxidant syrup through workshop activities held by a team from Zahra University (UNZAH), with resource persons from the Probolinggo Regency Health Office. The results of this assistance include several important achievements, namely: first, the cultivation of environmental cleanliness among PKK women with the habit of disposing of mangosteen peel waste in the place that has been provided, as well as the sorting of quality mangosteen peels for processing. Second, the implementation of a workshop on processing mangosteen peel waste into antioxidant syrup involving PKK women in Ranuagung Village, Tiris District, Probolinggo Regency. Third, laboratory tests were carried out on processed syrups that showed satisfactory results, with a detected germ contamination level of 0%. This study shows that the use of mangosteen peel waste as an antioxidant syrup is not only beneficial for health, but also has the potential to improve the economic welfare of the community by processing waste into high-value products.